Cognitive Functioning in Adults Aging with HIV: A Cross-Sectional Analysis of Cognitive Subtypes and Influential Factors - Pariya L. Fazeli; Michael Crowe; Lesley A. Ross; Virginia Wadley; Karlene Ball; David E. Vance (Journal of Clinical Research In HIV AIDS And Prevention, 2014)
Objective: This cross-sectional study examined cognitive subtypes and influential factors in HIV-positive (HIV+) adults. Method: Two-step cluster analysis was conducted on a neurocognitive test battery in a sample (N = 78) of adults and older adults with HIV (Mage = 46.1). Next, cognitive, functional, and mental and physical health differences were compared between the HIV+ clusters and an HIV- reference group (N = 84; Mage = 47.9). Results: A two-cluster solution emerged, with a lower performing cluster exhibiting poorer performance across all domains except psychomotor speed, and a “normal” cluster displaying similar performance as the HIV- group. The most influential factors to classification in the lower performing cluster were older age and presence of stroke and hypertension. There were trends for longer duration of HIV-infection, higher unemployment rates, and greater prevalence of Hepatitis C co-infection in the lower performing cluster. Conclusions: These findings suggest that there are not unique cognitive subtypes in HIV, but rather a subset of individuals who exhibit globally normal performance and those with below average performance. Older age and the related cardiovascular comorbidities of both aging and HIV medications may be key influential factors to variability in neurocognitive functioning in this population and thus should be considered in future studies. Implications for research and practice are provided.
Keywords: Cluster analysis